A facile approach for TiO2-based superhydrophobic–superhydrophilic patterns by UV or solar irradiation without a photomask. Issue 15 (6th February 2017) - Yanqing, Zhu; jifu, Shi; Qizhang, Huang; Leilei, Wang; Gang, Xu
Abstract : A novel and facile approach to produce TiO2 -based superhydrophobic–superhydrophilic patterns by UV or solar irradiation without a photomask is presented. Abstract : A novel and facile approach to produce TiO2 -based superhydrophobic–superhydrophilic patterns by UV or solar irradiation without a photomask is presented. The fabricated superhydrophobic–superhydrophilic patterns with excellent mechanical properties have long lifetimes in outdoor applications or other UV environments because of a self-supply of low surface tension material.